The Effects of Choice on Reading Engagement and Comprehension for Second- and Third-Grade Students: An Action Research Report - Julie Fraumeni-Mcbride (University of Kansas, 2017)
Poor literacy rates contribute to low school performance for children across America. In particular, low-income schools continue to struggle with declining literacy rates. Issues with literacy are often attributed to lack of reading comprehension. This study tested the effects of choice on reading comprehension in second- and third-grade students at a high-income school and a low-income school. Students were observed while reading silently and aloud to see if either method affected reading comprehension. Data were collected from 32 students before, during, and after reading to determine whether students' comprehension levels were higher when given opportunities to choose their own books or when they read assigned books. Trials were performed while students read silently and then aloud. Results indicated that students had higher comprehension levels both when they could choose their own books and when they read silently.